A construção do sucesso e os contratos comunicacionais presentes nos portais Folha de S. Paulo e Estadão - Mesquita, Ana Paula Soares (2018)
The research investigates the different discourses midiatics built around the success and the communication strategies linked to the stories of the Estadão and Folha de S. Paulo sites, published in the sections of culture and entertainment. The success here in this dissertation refers to the proposals or tips of the enunciator to the enunciative so that he has a life of success, be it professional, loving, financial, among others. The selected materials were those that thematic beauty, well-being, entertainment, celebrities and business, because they are news that call the users to achieve this success. Strategies involve the position of the enunciator, hypermedia structures, hypertexts, comments, website responses, uses of emojis, memes, gifs and social networks, especially on Facebook and Twitter social networks. It is intended to show in this work how the relentless pursuit of success is present daily in people's lives, through news from traditional newspapers. To work the calls and contracts will be used Prado (2013) and Fiorin (2014); for the concepts of discourse analysis Gregolin (1995), Charaudeau (2006) and Fiorin (2014); for the concepts of online journalism and hypermedia, multimedia and hypertext, Ferrari (2012) and Leão (1999) were used, and Estevanim (2016) was approached to conceptualize data journalism, also known as Big Data